Adaptation of mouse skeletal muscle to long-term microgravity in the MDS mission. - Dorianna Sandonà (PLoS ONE, 2012)
The effect of microgravity on skeletal muscles has so far been examined in rat and mice only after short-term (5-20 day) spaceflights. The mice drawer system (MDS) program, sponsored by Italian Space Agency, for the first time aimed to investigate the consequences of long-term (91 days) exposure to microgravity in mice within the International Space Station. Muscle atrophy was present indistinctly in all fiber types of the slow-twitch soleus muscle, but was only slightly greater than that observed after 20 days of spaceflight. Myosin heavy chain analysis indicated a concomitant slow-to-fast transition of soleus. In addition, spaceflight induced translocation of sarcolemmal nitric oxide synthase-1 (NOS1) into the cytosol in soleus but not in the fast-twitch extensor digitorum longus (EDL) muscle. Most of the sarcolemmal ion channel subunits were up-regulated, more in soleus than EDL, whereas Ca(2+)-activated K(+) channels were down-regulated, consistent with the phenotype transition. Gene expression of the atrophy-related ubiquitin-ligases was up-regulated in both spaceflown soleus and EDL muscles, whereas autophagy genes were in the control range. Muscle-specific IGF-1 and interleukin-6 were down-regulated in soleus but up-regulated in EDL. Also, various stress-related genes were up-regulated in spaceflown EDL, not in soleus. Altogether, these results suggest that EDL muscle may resist to microgravity-induced atrophy by activating compensatory and protective pathways. Our study shows the extended sensitivity of antigravity soleus muscle after prolonged exposition to microgravity, suggests possible mechanisms accounting for the resistance of EDL, and individuates some molecular targets for the development of countermeasures.